Claims for the Rights of Third Parties in Good Faith Against Confiscation of Goods in Corruption Criminal Decisions - Melkianus Ndaomanu (Unnes Law Journal, 2023)
The judge has the authority to impose additional criminal decisions in criminal acts of corruption in the form of confiscation of goods belonging to third parties in good faith. Article 19 Paragraph (2) of the Anti-Corruption Law states that third parties who have good intentions can claim their rights (object) to the confiscation of goods in a corruption crime decision no later than 2 (two) months after the court decision is pronounced in a hearing open to the public. However, the Corruption Law does not clearly regulate how to submit and examine objections so that in practice there are differences in interpretation by the applicant, respondent and judge in submissions and examinations at trial, so that there is no guarantee of unity and certainty in the legal application of rights claims (objections) to confiscation of goods in the decision of criminal acts of corruption. The legal problem that arises is what are the regulations regarding the submission and examination of claims (objections) of third parties who have good intentions regarding the confiscation of goods in the decision of a criminal act of corruption? Regulations regarding the submission and examination of claims for the rights of third parties in good faith regarding the confiscation of goods in decisions regarding criminal acts of corruption, including the legal position of the parties, method and time of submission, authority to adjudicate, evidence, and legal remedies and implementation of the decision.